Giant serous cystadenoma of the pancreas appearing sonographically as a remote pararenal mass. Issue 5 (25th March 2019) - Theodorou, Daphne J.; Theodorou, Stavroula J.; Kakitsubata, Yousuke; Miyata, Yuko; Shirao, Kazusada; Marutsuka, Kousuke
Abstract: Macrocystic serous cystadenoma (MSC) of the pancreas is a rare benign neoplasm with varied imaging appearances. We describe an intriguing case of a surgically resected and histologically proven giant MSC, developed in the pararenal space. Ultrasonography (US) revealed a large, oligocystic mass around the lower pole of right kidney. Like US, computed tomography, and magnetic resonance imaging were unable to detect the origin of the lesion, which was only verified at surgical exploration. A bizarre finding was the unusual location of the pancreatic tumor growing seemingly apart from the pancreas itself, with no obvious connection to it.